Relationship between Diet Quality and Nutritional Status among Adolescents - Lathifah, Nelda Nur; Wulansari, Arnati; Rahmawati, Helfi (Media Publikasi Cendekia Indonesia, 2024)
Adolescence is a transition period from childhood to adulthood. According to the World Health Organization (WHO), the limit for adolescents is between 10 - 19 years of age. Nutritional status in adolescents can influence growth and development and continue into adulthood. Low diet quality is one of the direct causes of nutritional status problems in adolescents. Data from the Jambi City Health Service in 2021 shows 280 cases of malnutrition at the junior high school and equivalent level in Jambi City. This research aims to determine the relationship between diet quality and nutritional status in adolescents at junior high schools of SMPN 9 Jambi City. The design used in this research was quantitative research with a cross-sectional approach. This research was carried out at SMPN 9 Jambi City in May 2023. The population and sample in this research were students of SMPN 9 Jambi City, totaling 88 people. The sampling technique was purposive random sampling. The data analysis used was univariate and bivariate. The highest frequency of diet quality was in the poor diet quality category, 52 respondents (59.1%). It can be concluded that a relationship exists between diet quality and nutritional status (p-value ≤ 0.05).